Monetary Policy Transmission : Does Maintain the Price and Poverty Stability is Effective? (JEJAK, 2018)
This study analyzes the effectiveness of monetary policy transmission of emerging market countries, both short and long-term in maintaining economic stability and reducing poverty. The main problem in this paper is that monetary transmission is incapable of controlling the economy and reducing poverty. There are five countries selected such as India, Brazil, China, Russia, and Indonesia. Long-term prediction analysis using Vector Auto Regression (VAR) model is performed to predict five emerging market countries using Regression Panel. It results suggest that monetary policy transmission affecting the number of poor people should be controlled in three stages. In the short-term, the transmission of export variables and inflation controls the number of poor people. In the medium-term, the control of the number of poor people uses variables of inflation and exports while in the long-term uses exports and Gross Domestic Product (GDP). Overall, all economic variables of emerging market countries are greatly influenced by the fluctuations of each country's exports, then by food price stability as measured by food price inflation. The result of regression panel analysis is known that the factor that most influence the poor people in emerging market country is GDP. Exports also affect poor people such as Indonesia, China, and Russia. Inflation also causes poor people like India and Brazil. The countries that have the most impact on economic fluctuations on the number of poor people are India, Indonesia, China, Brazil, and Russia.